Multicultural Education In The Perspective of National And Islamic Education - Heri Gunawan; Encep S Jaya (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This writing is backgrounded by the urgency of multicultural education implementation in Indonesia as the plural nation having the slogan of Bhineka Tunggal Ika (Unity in Diversity). The multicultural education discourse in Indonesia has been introduced since 1999 in the beginning of reformation era which has emerged the new paradigm in education from centralization to be decentralization. Various phenomena of tribes disputes, feeling and religion that happened, has strenghened the importance of multicultural education implementation at schools. This matter was aimed to educate the students with the sensitivity and care of their environement of multi-ethnic, culture, languange even the religion. So that they have capability of facing various social problems in their environment rooted from the difference. This matter can be implemented in the learning intergrally or showing up a new learning model which respect the people heterogenity. How is the concept of multicultural education in the perspective of national and Islamic education? The theme becomes the focus of this writing. It is necessary to find the correct and specific formulation on how the relevant multicultural education in the context of Indonesian society, as the society which has the high respect to the religious, morale, and eastern culture values. This condition is important so that the multicultural education resounded before in the western countries like America, Canada, and Australia do not “destroy” and “take” the Indonesian culture root. Key Words: Education, Multicultural, Plural, Globalization.